2005
DOI: 10.1042/bst0331182
|View full text |Cite
|
Sign up to set email alerts
|

Homoeostatic systems for sterols and other lipids

Abstract: Fatty acids and sterols are vital components of all eukaryotic cells. Both are used as building blocks for numerous cellular processes such as membrane biosynthesis or hormone production (sterols). Furthermore, these compounds elicit a variety of effects intracellularly as they can act as signalling molecules and regulate gene expression. The metabolism of fatty acids and sterols represents a very intricate network of pathways that are regulated in a precise manner in order to maintain lipid homoeostasis withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The microarray results reveal that the interaction between fatty acids and sterols is a complex network. It has been reported that each pathway is regulated in a precise manner in order to maintain lipid homoeostasis within a cell (Garbarino and Sturley, ). We built comprehensive gene networks in the above‐affected genes by using Pathway Studio ™ and observed down‐ or upregulation of lipid metabolism‐related genes as a consequence of ACC1 overexpression (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microarray results reveal that the interaction between fatty acids and sterols is a complex network. It has been reported that each pathway is regulated in a precise manner in order to maintain lipid homoeostasis within a cell (Garbarino and Sturley, ). We built comprehensive gene networks in the above‐affected genes by using Pathway Studio ™ and observed down‐ or upregulation of lipid metabolism‐related genes as a consequence of ACC1 overexpression (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise the metabolism of fatty acids and sterols represents a very intricate network of pathways that are regulated in a precise manner in order to maintain lipid homoeostasis within a cell. Furthermore, several links between the biosynthetic pathway of ergosterol and other pathways involved in the biosynthesis of lipids have been detected in recent investigations (Garbarino and Sturley, ; Veen and Lang, ). The knowledge of regulatory networks will be a major key for the systematic deregulation of the ergosterol biosynthetic pathway and the production of high‐value sterol metabolites with the yeast Saccharomyces cerevisiae .…”
Section: Introductionmentioning
confidence: 94%
“…Fatty acids (FAs) are a source of cellular energy and also serve as building blocks for a number of complex membrane lipids. Both fatty acids and sterols have the capacity to act as signaling molecules and to affect gene expression via upstream promoter elements (Garbarino and Sturley, 2005).…”
mentioning
confidence: 99%
“…During biogenesis, neutral-lipid-synthesizing enzymes generate lenses of neutral lipids that then bulge from the outer leaflet of ER. Indeed, recent studies in yeast have proved that LDs are absent in cells that cannot synthesize neutral lipids (Garbarino and Sturley, 2005;Sorger et al, 2004), highlighting the importance of neutral-lipid-synthesizing enzymes during LD biogenesis.…”
Section: Introductionmentioning
confidence: 99%